An updated feminist view of intimate partner violence - George, Jayashree; Stith, Sandra M. (My University, 2014)
In this article, we explore intimate partner violence (IPV) from an intersectional, feminist perspective. We describe how an updated feminist view guides us to a perspective on IPV that is more strongly grounded in an anti-oppressive, non-violent, socially just feminist stance than a second-wave gender-essential feminist stance that suggests that patriarchy is the cause of IPV. At the time we began to work together it seemed that a researcher had to be identified as a “family violence” researcher or a “feminist” researcher of violence against women, and that it wasn’t possible to be a feminist researcher who looked beyond patriarchy as the cause of IPV. We advocate critically thinking about essentialist practices in clinical work so that we can maintain an anti-oppressive, socially just, non-violent approach to working with clients who experience IPV.
Keywords: Intimate partner violence; Feminisms; Essentialism; Anti-oppression; Social justice